“SHАХS” LINGVISTIK ZАRRАSINING LEKSIK SATHDA АSSОTSIАTIV VOQELANISHI - Yigitaliyev, Umid (FILOLOGIYA UFQLARI JURNALI, 2022)
This article explores the associative-pragmatic expression of the language atom "man" at the lexical level of the Uzbek language through lexical units.